An oscillograms processing algorithm of a high power transformer on the basis of experimental data; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Vasilieva O. V. Olga Vladimirovna (Numerical Simulation of Applied Problems, 2016)
Title screen